Effect of Shenfu Injection on Reperfusion Injury in Patients Undergoing Primary Percutaneous Coronary Intervention for ST Segment Elevation Myocardial Infarction: A Pilot Randomized Clinical Trial - Wang, Xiao; Miao, Huangtai; Yan, Yan; Guo, Ruifeng; Gong, Wei; He, Yi; Wang, Hui; Ma, Xinliang; Nie, Shaoping (Frontiers in Cardiovascular Medicine, 2021)
Background: Shenfu injection is a traditional Chinese medicine formulation that alleviates ischemia-reperfusion injury through multiple pharmacologic effects. However, no data are available regarding its efficacy in patients with myocardial infarction. We aimed to examine the effects of Shenfu injection on infarct size in ST segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI). Methods: From April 2016 to February 2018, 40 patients with first-time anterior STEMI undergoing primary PCI within 6 hours of symptom onset were randomized 1:1 to intravenous Shenfu injection (80ml Shenfu injection+70ml 5% glucose injection) or placebo (150ml 5% glucose injection) before reperfusion. Treatment started before PCI and maintained for 5 days after PCI. The primary endpoints were infarct size as assessed by CK-MB area under the curve (AUC) over 72 h and cardiac magnetic resonance (CMR) at 4±1 days after PCI. Results: Infarct size by under the curve for CK-MB over 72 hours did not differ between Shenfu injection and placebo groups (5602.5 [3539.4-7526.4] vs. 6403.2 [2234.4-8340.6] ng·h/ml, P=0.82). Among 32 patients receiving CMR, a nominal reduction in infarct size was observed in Shenfu injection group compared with placebo group (23.9 [15.2-28.5] % vs. 27.0 [21.9-31.9] %, P=0.42). After excluding patients with no or minimal infarct, there was a trend towards a reduction in infarct size in Shenfu injection group (24.1 [20.3-29.3] % vs. 29.1 [24.5-32.0] %, P=0.18). Incidence of adverse events was similar between groups. Conclusions: This pilot study showed that the use of Shenfu injection was safe, but did not reduce infarct size by CMR and CK-MB release kinetics in reperfused STEMI patients. Larger study (confining to patients with extensive infarct size) to evaluate the efficacy of Shenfu injection on reperfusion injury are warranted.